2017
DOI: 10.3389/fpsyg.2017.01765
|View full text |Cite
|
Sign up to set email alerts
|

The Locus Preservation Hypothesis: Shared Linguistic Profiles across Developmental Disorders and the Resilient Part of the Human Language Faculty

Abstract: Grammatical markers are not uniformly impaired across speakers of different languages, even when speakers share a diagnosis and the marker in question is grammaticalized in a similar way in these languages. The aim of this work is to demarcate, from a cross-linguistic perspective, the linguistic phenotype of three genetically heterogeneous developmental disorders: specific language impairment, Down syndrome, and autism spectrum disorder. After a systematic review of linguistic profiles targeting mainly English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 97 publications
(99 reference statements)
0
10
0
Order By: Relevance
“…Recent comparative work that examined linguistic phenotypes across developmental disorders affecting language acquisition converged on the observation that narrow syntax (i.e., the internal computational system) tends to be more resilient than usually thought, i.e., likely to be preserved in many forms of developmental pathology, which by and large affect linguistic phenomena related to externalization, i.e., morphosyntax and morphophonology, linguistic domains that interface with the Intentional-Conceptual and Sensory-Motor systems (The Locus Preservation hypothesis; Leivada et al, 2017 ; Lorenzo and Vares, 2017 ) 10 . We would argue that dissociation in the patterns of language breakdown may reflect distinct underlying brain network organization corresponding to distinct evolutionary stages during which these linguistic domains emerged.…”
Section: Discussionmentioning
confidence: 92%
“…Recent comparative work that examined linguistic phenotypes across developmental disorders affecting language acquisition converged on the observation that narrow syntax (i.e., the internal computational system) tends to be more resilient than usually thought, i.e., likely to be preserved in many forms of developmental pathology, which by and large affect linguistic phenomena related to externalization, i.e., morphosyntax and morphophonology, linguistic domains that interface with the Intentional-Conceptual and Sensory-Motor systems (The Locus Preservation hypothesis; Leivada et al, 2017 ; Lorenzo and Vares, 2017 ) 10 . We would argue that dissociation in the patterns of language breakdown may reflect distinct underlying brain network organization corresponding to distinct evolutionary stages during which these linguistic domains emerged.…”
Section: Discussionmentioning
confidence: 92%
“…Future cross‐linguistic studies are needed to test to what extent other core grammatical structures, properties, or mechanisms that have been identified in typical language development may also be preserved in language acquisition of children with ASD learning a variety of languages. Such findings may provide evidence that the computational part of the human language faculty may be selectively preserved in at least some children with ASD across languages [Leivada, Kambanaros, & Grohmann, 2017; Su & Su, ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the behaviour of the disabled person is often not enough to change the non-disabled person's long-term socially constructed and ingrained beliefs about disability. It has been reported that even when there is a discrepancy between preconceived notions and new information, the preconceived notions prevail (Leivada et al 2017).…”
Section: The Construction Of Crip-dissonance the Creation And Manifes...mentioning
confidence: 99%